2016
DOI: 10.3389/fpsyg.2016.00134
|View full text |Cite
|
Sign up to set email alerts
|

Islands and Non-islands in Native and Heritage Korean

Abstract: To a large extent, island phenomena are cross-linguistically invariable, but English and Korean present some striking differences in this domain. English has wh-movement and Korean does not, and while both languages show sensitivity to wh-islands, only English has island effects for adjunct clauses. Given this complex set of differences, one might expect Korean/English bilinguals, and especially heritage Korean speakers (i.e., early bilinguals whose L2 became their dominant language during childhood) to be dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…After the first round of peer review in 2021, we recruited additional participants for the same experiments in order to improve the statistical power of our analyses. As such, our two experiments predate the experi-Scrambling dependencies are conventionally used to test island effects in Japanese due to the lack of overt wh-movement (for a discussion of island effects involving wh-in-situ, see Sprouse et al 2011;Kim & Goodall 2016;Tanaka & Schwartz 2018;Lu et al 2020). But before we move on to discuss our experiments, a caveat is in order concerning some characteristics of scrambling and the design of our experiments.…”
Section: The Motivation Of the Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…After the first round of peer review in 2021, we recruited additional participants for the same experiments in order to improve the statistical power of our analyses. As such, our two experiments predate the experi-Scrambling dependencies are conventionally used to test island effects in Japanese due to the lack of overt wh-movement (for a discussion of island effects involving wh-in-situ, see Sprouse et al 2011;Kim & Goodall 2016;Tanaka & Schwartz 2018;Lu et al 2020). But before we move on to discuss our experiments, a caveat is in order concerning some characteristics of scrambling and the design of our experiments.…”
Section: The Motivation Of the Current Studymentioning
confidence: 99%
“…We employed the factorial definition of island effects, both because we believe it matches the logic that has historically been used by syntacticians to define island effects, and because it allows us to eventually integrate our results with the growing cross-linguistic experimental literature using the factorial definition (a.o., Christensen et al 2013;5 Almeida 2014;Kim & Goodall 2016;Sprouse et al 2016;Keshev & Meltzer-Asscher 2018;Kush et al 2018;2019;Stepanov et al 2018;Tanaka & Schwartz 2018;Ko et al 2019;Lu et al 2019;Tucker et al 2019;Omaki et al 2020). As described below, we implement the factorial design completely within participants, allowing us to quantify to what extent each participant reports an island effect, so that we can investigate the conjecture from Yano (2019) that noun complements may show a higher degree of between-participant variability than other island types.…”
Section: The Logic Of the Designmentioning
confidence: 99%
“…Here too, acceptability experiments allow the kind of fine-grained analysis in which subtle differences among such groups can be detected (or ruled out). Kim and Goodall (2016), for instance, perform a series of acceptability experiments testing island phenomena in Korean using two groups of participants: native speakers of Korean residing in Korea and heritage speakers of Korean who were born in the US (or moved to the US before age 7) and who reside in the US. The results showed an intricate pattern of behavior across different island types, but this pattern was remarkably similar across the two populations, despite the very different linguistic environments that the two groups were exposed to in childhood.…”
Section: Comparing Populationsmentioning
confidence: 99%
“…First, FD-based experimental results are often interpreted and discussed only within the framework of syntactic approaches to island effects (e.g. Fukuda et al, 2021;Kim & Goodall, 2016;Kush et al, 2018Kush et al, , 2019Lu et al, 2020), which would be meaningful only if the island effects found in their experiments turn out to be syntactic in nature. For instance, Kush et al (2018) use the results of their experiments to evaluate the validity of different syntactic analyses of island effects (e.g.…”
Section: Biasmentioning
confidence: 99%
“…Since a factorial definition of island effects was first introduced by Sprouse (2007), it has become one of the most widely used experimental designs for investigating island-related phenomena in various languages, including Brazilian Portuguese, English, Hebrew, Italian, Japanese, Korean, Norwegian, Slovenian, and Spanish (e.g. Almeida, 2014;Fukuda et al (submitted); Keshev & Meltzer-Asscher, 2019;Kim & Goodall, 2016;Ko et al, 2019;Kush et al, 2018;Kush et al, 2019;Lee, 2018;Pañeda et al, 2020;Sprouse et al, 2016;Sprouse, 2007;Stepanov et al, 2018). The popularity the factorial design (henceforth, FD) enjoys is due to the fact that it helps to better understand island-related phenomena, which is possible thanks to its ability to isolate an island effect and measure its exact size.…”
Section: Introductionmentioning
confidence: 99%